SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN PINJAMAN MENGGUNAKAN METODE MULTIATTRIBUTE APPROXIMATION BORDER AREA COMPARISON (MABAC) - Iklima Ermis Ismail; Aisyah Dewi Hasanah (P3M Politeknik Negeri Indramayu, 2022)
The process of determining loan provision at Teacher Cooperative of SMAN 1 Jasinga is still using a manual system. Treasurer of Cooperative conduct the determining lending based on feasibility assessment of Cooperative members to receive loans without calculate the percentage of the borrower's eligibility value. This study aims to produce a Decision Support System (DSS) in assessing and ranking loan applications using the Multi-Attributive Border Approximation Area Comparison (MABAC) method in the Teacher Cooperative of SMAN 1 Jasinga. The MABAC method has 6 process steps, namely ordering the initial decision matrix, normalizing the initial matrix elements, calculating the weighted matrix elements, determining the area estimate matrix, calculating the alternative distance matrix elements from the border area and alternative ranking. The results of this study is a decision support system based on four predetermined criteria namely the purpose of loan, the amount of loan, the amount of saving and the amount of salary. This Decision Support System can accelerate the calculation process in determining loan provision by the Treasurer of Teacher Cooperative so that it becomes more efficient and right on target. Testing is done using 40 loan applications data. Based on the accuracy results of the comparison between the real data with DSS calculation data is obtained value 87.5%.